Interpretasi Maqashid Al-Qur’an terhadap Keadilan Distribusi Kekayaan pada Sistem Bitcoin dalam Transformasi Ekonomi Digital - Habitue, Healthy; Alhafiz, Muhammad; Rahmi, Azra Nadhilah; Muslim, Hanifah; Arfan, Khalisa Nurul Fitri; Latifa, Nur; Kurniawan, Dandi (An-Nahdloh: Journal of Education and Islamic Studies, 2026)
This study examines the justice of wealth distribution within the Bitcoin ecosystem using a maqāṣid al-Qur’an framework, with Surah al-Ḥasyr verse 7 serving as its primary ethical foundation. The study employs a qualitative method, based on a literature review and normative analysis, to assess whether Bitcoin’s ownership structure, transaction mechanisms, and market dynamics align with Islamic distributive justice principles. Data were gathered from digital economy literature, on-chain analytical reports, and contemporary studies on maqāṣid al-sharī‘ah. The findings reveal that although Bitcoin promotes technical decentralization, its asset distribution remains highly concentrated among a small group of holders, potentially intensifying digital inequality. The asset’s extreme price volatility further exposes small-scale users to significant financial instability. Within the maqāṣid framework, these conditions suggest that Bitcoin has not yet attained the level of public benefit necessary to ensure equitable access, fair distribution of value, and adequate protection of wealth. This study concludes that digital economic governance must be strengthened through inclusive policies, transparency mechanisms, and justice-oriented frameworks to minimize inequality and promote a more sustainable financial ecosystem. Keywords: Bitcoin, digital economy, wealth distribution, maqāṣid al-Qur’an, Surah al-Ḥasyr 7